2017
DOI: 10.1093/gastro/gox029
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of APACHE II, BISAP, Ranson’s score and modified CTSI in predicting the severity of acute pancreatitis based on the 2012 revised Atlanta Classification

Abstract: ObjectiveOur aim was to prospectively compare the Accuracy of Acute Physiology and Chronic Health Evaluation (APACHE) II, Bedside Index of Severity in Acute Pancreatitis (BISAP), Ranson’s score and modified Computed Tomography Severity Index (CTSI) in predicting the severity of acute pancreatitis based on Atlanta 2012 definitions in a tertiary care hospital in northern India.MethodsFifty patients with acute pancreatitis admitted to our hospital during the period of March 2015 to September 2016 were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
86
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 16 publications
9
86
1
6
Order By: Relevance
“…APACHEⅡ score is the most widely accepted and used scoring system, and is also a highly recommended scoring system by many guidelines [11]. SAP can be diagnosed when patients had an APACHEⅡ score of > 8, and those patients need to be transferred to ICU [12]. Study had shown that APACHE II score is a reliable scoring system, and has high sensitivity for assessing the severity, organ failure and death in AP [13].…”
Section: Discussionmentioning
confidence: 99%
“…APACHEⅡ score is the most widely accepted and used scoring system, and is also a highly recommended scoring system by many guidelines [11]. SAP can be diagnosed when patients had an APACHEⅡ score of > 8, and those patients need to be transferred to ICU [12]. Study had shown that APACHE II score is a reliable scoring system, and has high sensitivity for assessing the severity, organ failure and death in AP [13].…”
Section: Discussionmentioning
confidence: 99%
“…A score ≥ 8 is considered as a risk of death, and the risk is greater as the score increases. The APACHE-O is used when the obesity factor is added to the score [57][58][59][60]. c) Modified Glasgow Criteria (Imrie): Has sensitivity of 80% when used in the first 48 hours.…”
Section: Scoring Systemsmentioning
confidence: 99%
“…There are other scoring systems such as: i) Determinant-Based System: It is based on the identification of radiological changes of the collections, sterile PAN or infected and organ failure signs [66]. j) Severity index by CT: Sums the Balthazar degree, more the degree of necrosis [56,58,62,67]. Evaluates the presence of peripancreatic inflammation, phlegmon, and necrosis.…”
Section: Scoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is a reliable predictor of outcome. 4 Chatzicostas et al compared Ranson's score, APACHE II, and III and found all the three had similar predictability. 5 Recently, APACHE II and APACHE IV scores have been compared with a cutoff of 8 and 45, respectively, and the latter has a better diagnostic capacity than APACHE II, BISAP, and Ranson's criteria.…”
mentioning
confidence: 99%